Legal Protection Efforts and Islamic Business Ethics Analysis of Hidden Defect Products in Online Transactions - Al Islam, Harisma Annisa; Harahap, Sarah Khairani; Taufiq, M. (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
A hidden defective product in an online buying and selling transaction is selling a product whose condition is not in accordance with the original purpose of making the product. The product does not meet the proper product standards and has decreased function due to damage caused by the negligence of business actors, whether intentional or not. The most widely used platform in online buying and selling is personal media or social media, where there are only two parties to the trade agreement, namely business actors and consumers, so legal protection for consumers in this phenomenon is absolute and very much needed. The existence of a form of consumer loss from the case of hidden defective products certainly violates what is the provision of muamalah in sharia. Therefore, this research aims to analyze the application of Islamic business ethics to hidden defective products in online trade transactions and legal protection efforts that can be provided to consumers who suffer losses due to hidden defective products. This research uses the normative juridical analysis method to see the extent of legal protection efforts against consumers and how Islamic business ethics view the phenomenon. This study concludes that business actors who deliberately sell hidden products in online buying and selling clearly violate Islamic business ethics which prohibit hiding defective goods, unlike business actors who do not know the defects in the product, but business actors still have an absolute obligation to be responsible to consumers. The form of legal protection efforts for consumers of hidden defective products has been regulated in such a way in Law Number 8 of 1999 concerning Consumer Protection and the Civil Code. [Produk cacat tersembunyi dalam transaksi jual beli online adalah menjual produk yang kondisinya tidak sesuai dengan tujuan awal pembuatan produk. Produk tersebut tidak memenuhi standar produk yang semestinya dan mengalami penurunan fungsi akibat kerusakan yang disebabkan oleh kelalaian pelaku usaha, baik disengaja maupun tidak. Platform yang paling banyak digunakan dalam jual beli online adalah media personal atau sosial media, yang mana hanya terdapat dua pihak yang melakukan perjanjian perdagangan yaitu pelaku usaha dan konsumen, maka perlindungan hukum terhadap konsumen dalam fenomena ini bersifat mutlak dan sangat dibutuhkan. Adanya bentuk kerugian konsumen dari kasus produk cacat tersembunyi tentu saja melanggar apa yang menjadi ketentuan bermuamalah dalam syariat. Oleh karena itu, penelitian ini bertujuan untuk melakukan analisis terhadap penerapan etika bisnis Islam terhadap produk cacat tersembunyi dalam transaksi perdagangan secara online dan upaya perlindungan hukum yang dapat diberikan kepada konsumen yang mengalami kerugian akibat produk cacat tersembunyi. Penelitian ini menggunakan metode analisis yuridis normatif untuk melihat sejauh mana upaya perlindungan hukum terhadap konsumen dan bagaimana pandangan etika bisnis Islam terhadap fenomena tersebut. Penelitian ini menyimpulkan bahwa pelaku usaha yang sengaja menjual produk tersembunyi dalam jual beli online jelas melanggar etika bisnis Islam yang melarang untuk menyembunyikan barang cacat, berbeda halnya dengan pelaku usaha yang tidak mengetahui adanya cacat pada produk tersebut, namun pelaku usaha tetap memikul kewajiban mutlak untuk bertanggungjawab kepada konsumen. Adapun bentuk upaya perlindungan hukum bagi konsumen atas produk cacat tersembunyi telah diatur sedemikian rupa dalam Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen dan Kitab Undang-Undang Hukum Perdata.]